The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.5644/ama2006-124.47
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of transthoracic and transesophageal echocardiography in predicting the size of atrial septal defect

Abstract: Objective. To determine the reliability of transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE) in predicting the size of an atrial septal defect (ASD). Material and methods. The study included 16 patients who underwent the catheter-based procedures to close an atrial septal defect between February 2008 and December 2011 at the Paediatrics Clinic, CCU Sarajevo, after clinical and TTE and TEE evaluation. In order to determine the assumed diameter of the balloon (A-SBD), we used the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Some investigators have reported that transesophageal echocardiography and real-time three-dimensional ultrasound are more accurate than transthoracic echocardiography; [ 15 ] however, we believe that transthoracic echocardiography can be used for preoperative patient selection and intraoperative occluder placement with the assistance of an experienced ultrasonographer. [ 16 19 ] There have been many reports of follow-up of patients undergoing percutaneous ASD closure, most of these reports are concerned with residual shunting, occluder displacement, or thrombotic events. [ 20 , 21 ] Other investigators have reported results of echocardiography during postoperative follow-up of patients who have undergone percutaneous closure of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have reported that transesophageal echocardiography and real-time three-dimensional ultrasound are more accurate than transthoracic echocardiography; [ 15 ] however, we believe that transthoracic echocardiography can be used for preoperative patient selection and intraoperative occluder placement with the assistance of an experienced ultrasonographer. [ 16 19 ] There have been many reports of follow-up of patients undergoing percutaneous ASD closure, most of these reports are concerned with residual shunting, occluder displacement, or thrombotic events. [ 20 , 21 ] Other investigators have reported results of echocardiography during postoperative follow-up of patients who have undergone percutaneous closure of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…After reading the full text, 67+98 articles that could not obtain the full text and had an incomplete experimental design were eliminated. Finally, six articles were obtained [12][13][14][15][16][17]. The literature screening process is shown in Fig.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The demographic and baseline characteristics of the patients are shown in Table 1 (Ref. [12][13][14][15][16][17]). In the included literature, patients were divided into different groups based on the various types of echocardiography of the studies.…”
Section: Basic Characteristics and Quality Evaluation Of Included Lit...mentioning
confidence: 99%
See 1 more Smart Citation